Establishment of Proliferative Tetraploid Cells from Normal Human Fibroblasts - Ohshima, Susumu; Seyama, Atsushi (Frontiers in Oncology, 2013)
The chromosomal instability of polyploid cells, which leads to the formation of aneuploid cells, is causally related to carcinogenesis in human tissues. However, the precise link between the chromosomal instability of polyploid cells and oncogenic transformation of them remains elusive. This is partly because we lack an experimental model in which nontransformed polyploid human cells can propagate in vitro. In a previous report, we demonstrated that proliferative tetraploid cells can be established from TIG-1 human fibroblasts by treatment with the spindle poison demecolcine (DC, colcemid) for 4 days.. However, this procedure could not be applied to other human fibroblast strains because the resulting cells proliferated as a mixture of diploid and tetraploid populations. Here, we report a modified procedure to establish proliferative tetraploid cells from human fibroblasts of the BJ strain with minimum contamination by diploid cells. In the modified procedure, DC-arrested mitotic cells were collected by mitotic shake-off and treated with DC for an additional three days. DC-treated cells restarted proliferation as tetraploid cells after several days of growth arrest and showed similar growth to that of untreated diploid cells. The MDM2 antagonist Nutlin-3a activated p53 in established tetraploid cells and suppressed their growth, indicating that these cells have functional p53. These results contradicted the hypothesis that p53 functions as the tetraploidy checkpoint and prevents proliferation of tetraploid cells. Tetraploid cells established by our method could be a valuable model for the study of chromosomal instability and the oncogenic potential of polyploid cells.